P659 Continuing or stopping 5-aminosalicylate in patients with Inflammatory Bowel Disease under anti-TNF therapy: A nationwide population-based study. (30th January 2023) - Seo, J; Kim, S; Song, S; Shin, S H; Park, S; Hong, S W; Hwang, S W; Park, S H; Yang, D H; Byeon, J S; Myung, S J; Yang, S K; et al.
Abstract: Background: The clinical impact of continuing or stopping 5-aminosalicylate (5-ASA) after escalating to treatment with an anti-tumour necrosis factor (TNF) agent in patients with inflammatory bowel disease (IBD) is currently unclear. We aimed to compare the outcomes of IBD patients who stopped or continued 5-ASA after starting anti-TNF therapy. Methods: We analysed data obtained from the Korean National Health Insurance claims database between 2007 and 2020. Our analysis included IBD patients already on 5-ASA treatment who started anti-TNF treatment. We compared the prognosis of patients who stopped 5-ASA within 90 days of anti-TNF initiation with those who continued 5-ASA. The primary outcome was any adverse clinical event defined as a composite of intestinal surgery, IBD-related hospitalization, or new corticosteroid use. Kaplan-Meier method and Cox proportional hazards models at landmark time were used to calculate adjusted hazard ratios (aHRs) with 95% confidence intervals (CIs). Results: Among 62, 262 patients diagnosed with IBD during the study period, 7, 442 patients were included for analysis. A total of 1, 037 (13.9%) patients discontinued 5-ASA within 90 days of starting anti-TNF therapy (Figure 1). Among the included patients, 4, 479 (60.2%) had Crohn's disease, while 2, 963 (39.8%) had ulcerative colitis (Table 1). Discontinuation of 5-ASA was not associated with an increased risk of any adverse clinical events, as well as its component outcomes of intestinal surgery, IBD-related hospitalization, and corticosteroid use, with aHRs of 1.011 (95% CI, 0.934 to 1.095), 0.954 (95% CI 0.760 to 1.198), 0.995 (95% CI 0.894 to 1.107), and 0.969 (95% CI, 0.890 to 1.056), respectively (Table 2). In addition, the cumulative incidence of each adverse clinical event, as well as the composite outcome, were not significantly different between the two groups (all, p > 0.05) (Figure 2). Subgroup analysis by sex, IBD type, the timeframe of anti-TNF use, pre-anti-TNF 5-ASA use duration, pre-anti-TNF corticosteroid use, pre-anti-TNF hospitalizations, pre-anti-TNF emergency department visits, and anti-TNF agent type also showed no significant difference in the development of adverse clinical events between the two groups. Conclusion: In this nationwide population-based study, we observed that discontinuing 5-ASA after starting anti-TNF therapy was not associated with an increased risk of adverse clinical events.